Gender Differences in Academic Reading Attitudes among Undergraduates - Amri, Nur Arina Athirah Anuar; Fauzi, Nur Farahanim Mohd; Zaid, Najmi Najiha Mohd; Mee, Rita Wong Mee (Selangor Humaniora Review, 2021)
In Malaysia, reading attitudes among learners have always been linked together with their reading comprehension. Learners who read many kinds of different reading materials may better comprehend high order thinking skills (HOTS), speaking proficiency, and subject concepts. Thus, reading competency is essential as it will impact the learners’ intellect and broaden their sentiments. Learners who efficiently read will have higher chances to succeed, and the knowledge will be handy in the future. This study aimed to identify the reading attitude between male and female learners when reading English academic materials and investigate the effects of reading attitude towards male and female learners’ English reading comprehension in UNISEL, Bestari Jaya. The data was collected through a survey consisting of open-ended questions. The participants for this study were 110 undergraduate learners from UNISEL Bestari Jaya, Selangor. The findings show that female learners have a better reading attitude than male learners. However, it shows that the male learners would still involve themselves in reading activities depending on the types and elements of the reading materials. In conclusion, both male and female learners’ reading attitudes relate to their English reading materials preferences.